Foot Orgasm Syndrome: A Case Report in a Woman. (19th June 2013) - Waldinger, Marcel D.; de Lint, Govert J.; van Gils, Ad P.G.; Masir, Farhad; Lakke, Egbert; van Coevorden, Ruben S.; Schweitzer, Dave H.
Abstract: Introduction: Spontaneous orgasm triggered from inside the foot has so far not been reported in medical literature. Aims: The study aims to report orgasmic feelings in the left foot of a woman. Methods: A woman presented with complaints of undesired orgasmic sensations originating in her left foot. In‐depth interview, physical examination, sensory testing, magnetic resonance imaging (MRI‐scan), electromyography (EMG), transcutaneous electrical nerve stimulation (TENS), and blockade of the left S1 dorsal root ganglion were performed. Main Outcome Measures: The main outcomes are description of this clinical syndrome, results of TENS application, and S1 dorsal root ganglion blockade. Results: Subtle attenuation of sensory amplitudes of the left suralis, and the left medial and lateral plantar nerve tracts was found at EMG. MRI‐scan disclosed no foot abnormalities. TENS at the left metatarso‐phalangeal joint‐III of the left foot elicited an instant orgasmic sensation that radiated from plantar toward the vagina. TENS applied to the left side of the vagina elicited an orgasm that radiated to the left foot. Diagnostic blockade of the left S1 dorsal root ganglion with 0.8 mL bupivacaine 0.25 mg attenuated the frequency and intensity of orgasmic sensation in the left foot with 50% and 80%, respectively. Additional therapeutic blockade of the same ganglion with 0.8 mL bupivacaine 0.50 mg combined with pulsed radiofrequency treatment resulted in a complete disappearance of the foot‐induced orgasmic sensations. Conclusion: Foot orgasm syndrome (FOS) is descibed in a woman. Blockade of the left S1 dorsal root ganglion alleviated FOS. It is hypothesized that FOS, occurring 1.5 years after an intensive care emergency, was caused by partial nerve regeneration (axonotmesis), after which afferent (C‐fiber) information from a small reinnervated skin area of the left foot and afferent somatic and autonomous (visceral) information from the vagina on at least S1 spinal level is misinterpreted by the brain as being solely information originating from the vagina.Waldinger MD, de Lint GJ, van Gils APG, Masir F, Lakke E, van Coevorden RS, and Schweitzer DH. Foot orgasm syndrome: A case report in a woman. J Sex Med 2013;10:1926–1934.